Walking the Gendered Tightrope Theresa May and Nancy Pelosi as Legislative Leaders - Haussman, Melissa (The CAWP Series in Gender and American Politics, 2023)
Walking the Gendered Tightrope analyzes the gendered expectations for women in high offices through the examples of British Prime Minister Theresa May and U.S. Speaker of the House Nancy Pelosi. Even at their highest positions, and while completing their greatest achievements, both May and Pelosi faced gendered critiques and intraparty challenges to their leadership. While other books have analyzed the barriers to higher office that women face, this book reveals how women in positions of power are still forced to balance feminine stereotypes with the perception of power as masculine in order to prove their legitimacy. By examining intraparty dynamics, this book offers a unique comparison between a majoritarian presidential and Westminster parliamentary system. While their parties promoted Pelosi and May to highlight their progressive values, both women faced continually gendered critiques about their abilities to lead their caucuses on difficult policy issues, such as the Affordable Care Act and two Trump impeachment votes for Nancy Pelosi, or finishing Brexit for Theresa May. Grounded in the legislative literature from the United States and Britain, as well as historical accounts and personal interviews, Walking the Gendered Tightrope contributes to the fields of gender and politics, legislative studies, American politics, and British politics.